The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmicb.2020.01706
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Legacy Effects Following the Agia Zoni II Oil-Spill, Greece

Abstract: In September 2017 the Agia Zoni II sank in the Saronic Gulf, Greece, releasing approximately 500 tonnes of heavy fuel oil, contaminating the Salamina and Athens coastlines. Effects of the spill, and remediation efforts, on sediment microbial communities were quantified over the following 7 months. Five days post-spill, the concentration of measured hydrocarbons within surface sediments of contaminated beaches was 1,093-3,773 µg g −1 dry sediment (91% alkanes and 9% polycyclic aromatic hydrocarbons), but measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 111 publications
0
18
2
Order By: Relevance
“…Comparatively, a study within the Gulf of Mexico revealed that sediments around the shipwreck of the oil-tanker "Halo" (sunk May 1942) contained PAH concentrations ranging approximately 0-1,400 µg kg −1 of dry sediment respectively, resulting in an EIHE of 0.025 (see Figure 5 and Supplementary Table 3; Hamdan et al, 2018), twofold higher than the EIHE observed in surface sediments around HMS Royal Oak. Additionally, contaminated sediments sampled 5 days after the Agia Zoni II oil-spill, which contained average PAH concentrations of 210,000 µg kg −1 of dry sediment, resulted in an EIHE of 0.52, 42-fold higher than the EIHE observed in surface sediments of the present study (see Figure 5D and Supplementary Table 3; Thomas et al, 2020).…”
Section: Bacterial 16s Rrna Gene Analysis Reveals Low Levels Of Hydrocarbon-degrading Bacteriacontrasting
confidence: 57%
See 3 more Smart Citations
“…Comparatively, a study within the Gulf of Mexico revealed that sediments around the shipwreck of the oil-tanker "Halo" (sunk May 1942) contained PAH concentrations ranging approximately 0-1,400 µg kg −1 of dry sediment respectively, resulting in an EIHE of 0.025 (see Figure 5 and Supplementary Table 3; Hamdan et al, 2018), twofold higher than the EIHE observed in surface sediments around HMS Royal Oak. Additionally, contaminated sediments sampled 5 days after the Agia Zoni II oil-spill, which contained average PAH concentrations of 210,000 µg kg −1 of dry sediment, resulted in an EIHE of 0.52, 42-fold higher than the EIHE observed in surface sediments of the present study (see Figure 5D and Supplementary Table 3; Thomas et al, 2020).…”
Section: Bacterial 16s Rrna Gene Analysis Reveals Low Levels Of Hydrocarbon-degrading Bacteriacontrasting
confidence: 57%
“…Analysis of OHCB genera revealed only a sporadic and very low abundance of FIGURE 5 | Ecological Index of Hydrocarbon Exposure (EIHE) (ratio up to 1) representing relative abundance of oil-degrading/associated Bacteria, (Lozada et al, 2014) measurements (±SE, n = 4), for sediments sampled around the shipwreck HMS Royal Oak (located in Scapa Flow, Scotland, United Kingdom, November 2019), over a 17.5 cm depth profile (A), a 950 m transect (where sediments further away act as controls) (B), and given the transect direction (C). Additionally, a comparison between the HMS Royal Oak EIHE and other studies investigating oil-polluted environments (D): "HMS Royal Oak" (present study, surface sediments), "Halo" (Hamdan et al, 2018), "Patagonian Coast" (Lozada et al, 2014), "Brazilian Mangrove" (Dos Santos et al, 2011), "Colne Estuary" (Coulon et al, 2012), "Ushuaia Bay (no nutrients)", "Pensacola Beach" (Kostka et al, 2011), "Agia Zoni II" (Thomas et al, 2020) and "Ushuaia Bay (added nutrients)" (Guibert et al, 2012).…”
Section: Bacterial 16s Rrna Gene Analysis Reveals Low Levels Of Hydrocarbon-degrading Bacteriamentioning
confidence: 93%
See 2 more Smart Citations
“…γ-Protobaceria-affiliated Marinobacterium , Marinobacter , Pseudomonas , and Halomonas were dominant in ABRS and ABRW. Nearly all the sequences of the γ-protobaceria-affiliated OTUs showed the closest similarities to the sequences detected from oil-related environments ( S2 Fig ) and possess the ability to degrade hydrocarbons or polymers [ 33 , 34 ]. Another main group of hydrocarbon-degrading microbes were δ-protobaceria-affiliated Desulfotignum and Desulfoglaeba .…”
Section: Resultsmentioning
confidence: 99%